PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN POLITIK BERBASIS PARTISIPASI SISWA DALAM PKN (STUDI PADA SISWA SMA NEGERI 3 SUKOHARJO) - Suryaningsih, Anis (PKn Progresif, 2015)
This study aims to: (1) To develop a learning model based Political Education in civics student participation in accordance with the conditions of SMA Negeri 3 Sukoharjo. (2) Describe the steps Political Education learning models based on participation of students in Civics in accordance with the conditions of SMA Negeri 3 Sukoharjo. (3) Describe the feasibility of developing a learning model based on student participation Political Education in Civics in accordance with the conditions of SMA Negeri 3 Sukoharjo. This study uses the research or development of Research and Development. Data analysis is an interactive model of analysis of data reduction, data presentation and conclusion. Research procedures using the steps preliminary study phase, development and testing. Based on these results it can be concluded that: (1) High School Civics Teacher Interior 3 Sukoharjo desperately need civics learning models that optimize student participation in the learning of political education. These needs can be equipped with developing learning models that are tailored to the conditions of SMA Negeri 3 Sukoharjo. (2) The steps of Politics Partisipare learning model is as follows: (a) Planning Phase (b) Implementation Phase (c) Evaluation Phase. (3) Of all the due diligence has been carried out by researchers generate that the learning model is on average rated as excellent and worthy by a team of experts, teachers and students so as to promote student participation in politics with through civics education.